Technology Acceptance Model on Village Financial System in Minimizing Fraudulent Practices by Village Apparatus - Julia, Hany Nanda (Research Collaboration Community (Rescollacom), 2025)
This study aims to examine the implementation of the village financial system in minimizing fraudulent practices by village apparatus using the Technology Acceptance Model (TAM) approach in Padaasih Village, Cisaat District, Sukabumi Regency. This research uses a descriptive qualitative method. The informants involved in this study are village apparatus who are directly engaged with the management of the village financial system as part of the village budget management. This study finds that, overall, the implementation of the village financial system in minimizing fraudulent practices by village apparatus using the Technology Acceptance Model (TAM) approach has been carried out in accordance with the framework designed to control fraudulent practices at the village level. However, some aspects still show weaknesses in supervising fraudulent behavior, mainly due to the perceived insufficient quality of human resources. Field findings indicate that fraudulent practices do exist in village budgeting, although they are considered minimal. Training and workshops aimed at improving the quality and skills of village apparatus in overseeing village budget preparation through the village financial system are necessary. Additionally, the active participation of the community in monitoring the implementation of village programs should be maximized, from pre-budget preparation to post program realization. This study monitors and evaluates the implementation of the village financial system in minimizing fraudulent practices by village apparatus using the Technology Acceptance Model (TAM) approach.